Karyotype of Propsilocerus akamusi (Tokunaga) from China (Diptera: Chironomidae) - Kiknadze, Iya I.; Wang, Xinhua; Istomina, Albina G. (Zootaxa, 2004)
The karyotype structure and banding patterns of the polytene chromosomes of Propsilocerus akamusi from China are investigated for the first time. Photographic maps of the three chromosomes of P. akamusi are presented. Three heterochromatic blocks in the centromere regions are characteristic of this species. Chromosomal polymorphisms were not found in the Chinese populations. Cytogenetic data support the phylogenetic argument previously outlined for the genus.